2013
DOI: 10.1111/iep.12051
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiological properties of the ubiquitin ligase Nedd4L in melanoma

Abstract: A recent global gene expression profiling study unexpectedly showed that activated oncogenic NRAS may recruit neural precursor cell expressed, developmentally downregulated 4L (Nedd4L; a human homologue of Nedd4-2) in cultured melanoma cells. However, whether Nedd4L was expressed in melanoma tissues or participated in melanoma carcinogenesis remains to be clarified. Here, we investigated the expression status of Nedd4L in human melanocytes, benign nevi and melanoma tissue specimens and subsequently attempted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…However, there are also reports showing an increased expression of NEDD4L in prostate cancer (32). Expression of NEDD4L was also seen in a portion of melanoma samples but not detected in non-tumorous melanocytes or benign nevi tissues (33). These results indicate a potentially complex role of NEDD4L in the development of cancer.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, there are also reports showing an increased expression of NEDD4L in prostate cancer (32). Expression of NEDD4L was also seen in a portion of melanoma samples but not detected in non-tumorous melanocytes or benign nevi tissues (33). These results indicate a potentially complex role of NEDD4L in the development of cancer.…”
Section: Discussionmentioning
confidence: 73%
“…6), decreased cell size and colony formation ability (Fig. 8), and significantly reduced the growth of melanoma cells (33), suggesting a positive role of NEDD4L in maintaining the strength of PI3K-AKT signaling. However, partial down-regulation of NEDD4L seen in many cancers may lead to an increase in PIK3CA protein level that probably promotes cell growth, suggesting a tumor suppressing role of NEDD4L through promoting PIK3CA degradation.…”
Section: Discussionmentioning
confidence: 92%
“…Increased NEDD4L level was also reported in many cases of cutaneous invasive and nodal metastatic melanoma, but not in non-tumorous melanocytes or benign tissue specimens [68]. Immunohistochemical staining revealed that NEDD4L was present in 34 out of 79 cutaneous melanomas and in 9 of 32 nodal metastatic melanomas, while undetected in any non-tumorous melanocytes or in benign nevi tissues.…”
Section: Nedd4l (Nedd4-2)mentioning
confidence: 79%
“…Immunohistochemical staining revealed that NEDD4L was present in 34 out of 79 cutaneous melanomas and in 9 of 32 nodal metastatic melanomas, while undetected in any non-tumorous melanocytes or in benign nevi tissues. Consequently, silencing of NEDD4L expression significantly reduced the melanoma cells growth; whereas NEDD4L overexpression accelerated it both in culture and in mice [68].…”
Section: Nedd4l (Nedd4-2)mentioning
confidence: 95%
“…As an E3 ubiquitin ligase of the Nedd4 family, Nedd4-2 probably modulates and binds to multiple membrane proteins to aid in their internalization and turnover (5,6). Dysfunctions of Nedd4-2 have been implicated in many human pathologies through the targeted membrane proteins; for example, inhibition of the interaction between Nedd4-2 and epithelial sodium channel (ENaC) leads to Liddle's syndrome (7), downregulation of voltage-gated sodium channels by Nedd4-2 contributes to neuropathic pain (8), altered levels of Nedd4-2 are linked to multiple tumor types (9,10) and genetic variation in Nedd4-2 is associated with hypertension (11). Therefore, the present study examined post-translational modifications to explore the potential mechanism of 20-HETE-regulated Nedd4-2 expression in the CYP4F2 transgenic mouse model.…”
Section: Introductionmentioning
confidence: 99%